Analisa Interaksi Hidrofobik terhadap Kestabilan Termal Enzim Xilanase Aspergillus niger - Nya Daniaty Malau; Manogari Sianturi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2019)
Xylanase is one type of enzyme that has an important role in the field of industry. One way that can be done to improve the thermostability of an enzyme is by protein engineering . Mutation of these proteins can be done by studying the structure of proteins through molecular dynamics simulation approach. In this research, thermal stability analysis on the structure of Aspergilus niger Wild Type xylase (AnX) was performed. This study aims to study the thermal stability characteristic of Aspergilus niger xylanase enzyme through molecular dynamics simulation approach. Molecular dynamics simulations of AnX were performed using NAMD (Not Just Another Molecular Dynamic) software at at a temperature of 300-500 K. This study focused on studying the thermal stability characteristic of the enzymes to obtain information on residues that are responsible for the characteristic. Selection of residues to be mutated, based on the results of Hydrophobic Interactions. Based on the analysis results, the design of mutant Xylanase enzyme that is more thermostable than the Wild Type Xilanase Enzyme, so it can provide suggestions a more stable Xilanase mutation design that can be implemented into wet experiments to genetically engineer the Aspergilus niger xylanase enzyme. Xylanase Aspergillus niger enzyme is unfolded at 500 K at 9.5 ns. The residues responsible for the thermal stability of Xilanase Aspergilus niger enzyme based on hydrophobic interaction analysis are Alanine at residue 60. This residue is in segment / chain 3. The best mutant that can increase thermal stability is indicated by the Alanin 60 residue replaced with Methionin. The mutant Alanin 60 residue that replaced with a methionine mutant obtained Î”Î”Gsolv value of -21.10345. Thus the Ala60Met mutant is the most stable mutant supposed to increase thermal stability of Aspergillus niger Xilanase Enzyme. Keywords : enzyme, thermostability, mutation, molecular dynamics